(untitled) (Revista INFAD de Psicología. International Journal of Developmental and Educational Psychology., 2015)
The main aim of this research is study the role of entrepreneurial education in academic wellbeing and burnout prevention. Based upon the existing literature, it has been reached the elaboration of several hypothesis; first of all the existence of a high level of entrepreneurial motivations among students as well as a low level of academic burnout in a condition of organizational wellbeing. Hence, the further hypothesis that between the two constructs there is a direct correlation of negative sign and the conclusion that where these requisites are present university is effectively entrepreneurial and in condition of academic wellbeing.